2020
DOI: 10.1016/j.jccase.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Successful trans-maternal nadolol pharmacotherapy in a fetus presenting with long QT syndrome type 2 complicated by torsade de pointes

Abstract: Fetuses with congenital long QT syndrome (LQTS) may experience life-threatening arrhythmias, such as torsade de pointes (TdP), and/or functional atrioventricular block. However, trans-maternal pharmacotherapy for these cases is rarely reported and management practices have yet to be established. The fetus of a mother with genetically-confirmed LQTS type 2 (LQT2) presented with complex arrhythmias, diagnosed via magnetocardiography as ventricular arrhythmias (including TdP), at 28 weeks of gestation. After init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It may be diagnosed prenatally with a family history, a characteristic arrhythmia, bradycardia, and associated findings such as AV block or torsades de pointes (TdP). One case of iLQTS was reported to be treated with trans-maternal nadolol, which was shown to be effective in the restoration of fetal sinus rhythm [ 80 ]. A review examining beta-blocker usage in pregnant women with iLQTS observed the subsequent effects on the uterus, fetal birth weight, and fetal glycemic levels.…”
Section: Reviewmentioning
confidence: 99%
“…It may be diagnosed prenatally with a family history, a characteristic arrhythmia, bradycardia, and associated findings such as AV block or torsades de pointes (TdP). One case of iLQTS was reported to be treated with trans-maternal nadolol, which was shown to be effective in the restoration of fetal sinus rhythm [ 80 ]. A review examining beta-blocker usage in pregnant women with iLQTS observed the subsequent effects on the uterus, fetal birth weight, and fetal glycemic levels.…”
Section: Reviewmentioning
confidence: 99%